Infection and immunity: 'There Are Things Out There You (Don't) Need To Know About'. (19th July 2022) - Afonina, Inna S.; Hoffmann, Eik
Abstract : This Special Issue of The FEBS Journal consists of 20 reviews covering various aspects and new developments in 'Infection and Immunity'. The issue includes expert views on the role of different immune cell populations, on the regulation of innate and adaptive immune responses, and novel concepts in host defence and inflammatory signalling. Many reviews in this issue also highlight potential targets for future therapeutic interventions that aim to tackle inflammatory and immune responses in health and disease Abstract : The latest Special Issue of The FEBS Journal, introduced here by Inna Afonina and Eik Hoffmann, consists of 20 reviews covering various aspects and new developments in 'Infection and Immunity'. The issue includes expert views on the role of different immune cell populations, on the regulation of innate and adaptive immune responses, and novel concepts in host defence and inflammatory signalling. Many reviews in this issue also highlight potential targets for future therapeutic interventions that aim to tackle inflammatory and immune responses in health and disease.